Seasons that will never return: The impact of farm mechanization on employment, incomes and population distribution - De Klerk, Mike (My University, 1984)
The study on which this paper is based is set out to assess the nature and strength of the link between recent changes in agricultural technology and employment in South Africa. Amongst its objectives were to determine the degree to which mechanisation has occurred on maize farms in recent years, how the labour process has changed, - changes in the level of employment and the characteristics of farm workers, - the causes of mechanisation, and whether any decline in employment has led to a rise in unemployment. From the findings, it was possible to make a number of deductions about changes in the geographical distribution of the population and in the incomes of farm workers and their families.
African Studies Seminar series. Paper presented 14 May, 1984.